Lead-free powder glass for stabilizing surface of mesa-type semiconductor device and application of lead-free powder glass
By sintering crystalline lead-free powder glass at 700-750°C, combining substrate powder with ZnO, B2O3, SiO2 and other components and crystalline powder containing zinc oxide, the problems of high expansion coefficient, high sintering temperature and low electrical characteristics of lead-free glass powder are solved, and the thermal expansion coefficient and high voltage resistance similar to that of semiconductor device silicon wafers are achieved.
Patent Information
- Application Number
- CN202411970233.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-21
AI Technical Summary
The existing lead-free glass powder has problems such as high expansion coefficient, high sintering temperature and low electrical characteristics, making it difficult to achieve stable coverage and high voltage withstand voltage on semiconductor devices.
By sintering the crystalline lead-free powder glass at a relatively low temperature of 700 to 750°C, base material powder with components such as ZnO, B2O3, SiO2 is used, and crystallized powder containing zinc oxide such as Zn4B6O13 is introduced, and the particle size is controlled to achieve uniform crystallization and high electrical characteristics.
The thermal expansion coefficient similar to that of the silicon wafer of semiconductor devices is achieved, the silicon wafer is avoided, and the forward and reverse pressure resistance is improved, and the acid resistance is excellent.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a semiconductor device passivation material, in particular to a lead-free powder glass for stabilizing the surface of a mesa-type semiconductor device and an application thereof. Background Art
[0002] Semiconductor devices containing PN junctions, especially mesa-type, rectifier diodes, thyristors, bidirectional thyristors, and triodes, will be directly covered with glass powder (or powdered glass) on the PN junction to prevent the degradation of semiconductor devices caused by external reasons, so as to provide a high-reliability semiconductor with stable surface and unaffected by time. The above-mentioned glass powder used for surface stability of semiconductor devices requires the following properties: 1) The thermal expansion coefficient is similar to that of the silicon wafer of the semiconductor device; 2) The electrical characteristics of the semiconductor device, that is, the forward and reverse voltage withstand voltage is high; 3) To prevent the degradation of the semiconductor device, the sintering temperature of the glass powder should be as low as possible (preferably below 800°C); 4) It does not contain alkaline impurities such as Na, K, Li and metal impurities such as Fe, Cr, and Cu that have adverse effects on semiconductor devices; 5) Excellent acid resistance, etc.
[0003] At present, the mainstream of semiconductor device glass powder is lead-based glass powder, whose main components are PbO-SiO 2 -Al 2 O 3 and PbO-B 2 O 3 -SiO 2 -Al 2 O 3 . The main reasons for using lead-based glass powder are as follows: 1) The thermal expansion coefficient is small, and when it is covered on a semiconductor device, the silicon wafer, which is the material of the semiconductor device, rarely warps or cracks; 2) The electrical properties of the semiconductor device, that is, the forward and reverse voltage resistance are high; 3) Due to its excellent acid resistance, it is not easy to cause property degradation in the semiconductor process using chemical treatment. However, in recent years, due to the harmfulness of lead oxide (PbO) containing lead components, the trend of not allowing the use of lead-based glass powder is accelerating. Based on this, the main component is ZnO-B 2 O 3 -SiO 2 Zinc-based glass powder has been developed and used. Zinc-based glass powder contains a small amount of lead oxide, or no lead oxide at all, and will not cause crystallization. When used, it will show the same excellent electrical properties as lead-based glass powder, but due to its high expansion coefficient, it is easy to cause the silicon wafer used as a semiconductor device material to warp and crack. By reducing the expansion coefficient by crystallizing zinc-based glass powder, the warping and cracking of silicon wafers can be reduced, but its electrical properties, that is, the forward and reverse withstand voltages, will have the problem of reduced withstand voltage due to crystallization, resulting in zinc-based glass powder being used only in limited semiconductor devices.
[0004] Currently, research is underway to 2 -B 2 O 3 -Al 2 O 3 Glass powder is used as a glass powder for semiconductor coating. It does not contain lead and has the same excellent acid resistance as lead-based glass powder. However, because it contains a large amount of SiO 2 and Al 2 O 3 Therefore, the sintering temperature of glass powder needs to reach above 900℃, which not only easily causes the degradation of semiconductor devices, but also has poor contact with semiconductor devices. The electrical properties, namely the forward and reverse voltage resistance, are not high, and the leakage current is also large. Therefore, glass powder that can actually be used in semiconductor devices has not yet been available. Summary of the invention
[0005] In view of the problems of high expansion coefficient, high sintering temperature and low electrical properties of the above-mentioned lead-free glass powder, the present invention provides a lead-free powder glass with stable surface for table-type semiconductor devices and its application. The powder glass does not contain lead components, and is crystallized after sintering at a relatively low temperature of 700-750°C, so that its expansion coefficient is close to that of silicon wafers used as semiconductor device materials. After covering the surface of the silicon wafer, the wafer will not warp or crack. At the same time, it has unprecedented excellent electrical properties such as high voltage resistance after crystallization and excellent acid resistance.
[0006] In order to achieve the above object, the present invention provides a lead-free powder glass for stabilizing the surface of a mesa-type semiconductor device, which comprises a base material powder and a crystalline powder containing zinc oxide. The base material powder comprises 50-70% ZnO, B 2 O 3 5~22%, SiO 2 15~25%, R x O y 0.01~5%, and Y 2 O 3 and / or GeO 2 0~15%, of which R x O y SnO 2 、In 2 O 3 、ZrO 2 、TiO 2 、Bi 2 O 3 ,La 2 O 3 、Nd 2 O 3 At least one of; the zinc oxide crystalline powder is Zn 4B 6 O 13 、Zn 3 B 2 O 6 、Zn 3 (BO 3 ) 6 、Zn 4 O(BO 2 ) 6 , ZnB 4 O 7 、Zn(BO 2 ) 2 At least one of the above, relative to 100g of the base material powder, the amount of the zinc oxide-containing crystalline powder is 0.01-5g.
[0007] In the above-mentioned base powder, ZnO is a component that stabilizes the glass powder contained in a large amount in the glass powder component, and is also a component that affects crystallization. The ZnO content is 50-70%, preferably 55-70%. When it is less than 50%, it is difficult to crystallize; when it is more than 70%, it is difficult to obtain uniform glass powder.
[0008] B 2 O 3 Like ZnO, it is a component that affects crystallization. 2 O 3 The content of is preferably between 5 and 22%. When it is less than 5%, it is easy to form stones during the melting of glass powder, and it is difficult to obtain uniform glass powder. When it is greater than 22%, it is difficult to crystallize.
[0009] SiO 2 It is a component that stabilizes the structure of glass powder and improves acid resistance. 2 The content of SiO is preferably between 15% and 25%. When it is less than 15%, the thermal expansion coefficient after crystallization increases and the acid resistance is weak. When it is greater than 25%, SiO 2 Undissolved matter will be produced during melting, and uniform glass powder cannot be obtained.
[0010] In order to make the glass homogenous, add 0-15% Y 2 O 3 and GeO 2 Or choose one. Especially containing more than 20% SiO 2 The composition effect is large. If Y 2 O 3 and / or GeO 2 If the content is above 15%, the glass will become hard and the sintering temperature of the glass will increase.
[0011] In addition, SnO 2 、In 2 O 3 、ZrO2 、TiO 2 、Bi 2 O 3 ,La 2 O 3 、Nd 2 O 3 Each component is an important component that can improve the forward and reverse withstand voltage after crystallization. Contains one or more SnO 2 、In 2 O 3 、ZrO 2 、TiO 2 、Bi 2 O 3 ,La 2 O 3 、Nd 2 O 3 The content is 0.01 to 5 weight percent, and 0.01 to 3 weight percent is particularly recommended. If it is less than 0.01%, the reverse withstand voltage is not high. If it is greater than 5%, undissolved matter is generated during the melting of the glass powder, and a uniform glass powder cannot be obtained.
[0012] In order to improve the electrical properties, it is necessary to precipitate dense and uniform crystals after the glass powder is fired. 4 B 6 O 13 、Zn 3 B 2 O 6 、Zn 3 (BO 3 ) 6 、Zn 4 O(BO 2 ) 6 , ZnB 4 O 7 、Zn(BO 2 ) 2 At least one crystal of the above is added to the glass powder of the present invention, and dense crystals are precipitated from the surface of the glass powder by adding ZincBorate crystals with different crystal structures.
[0013] In order to obtain uniform crystals, the D50 particle size of the glass powder must be 1 to 10 μm. If it is less than 1 μm, the amount of crystallization is large, the fluidity is poor, and it does not adhere closely to the semiconductor element. If it is more than 10 μm, the fluidity and crystallization are insufficient, the leakage current of the semiconductor element becomes large, and the withstand voltage is not high.
[0014] The ZnO-containing Zn 4 B 6 O 13 、Zn 3 B2 O 6 、Zn 3 (BO 3 ) 6 、Zn 4 O(BO 2 ) 6 , ZnB 4 O 7 、Zn(BO 2 ) 2 One or more of the crystalline powders are mixed into the glass powder component, and 0.01 to 5 grams, preferably 0.01 to 3 grams, are mixed into 100 grams of the glass powder. If the individual crystals are less than 0.01%, they cannot be fully crystallized, and the thermal expansion coefficient will not decrease, so that the thermal expansion coefficient close to that of the semiconductor device silicon wafer cannot be obtained. On the other hand, if it is greater than 5%, the crystallization is too strong, the fluidity of the glass powder is poor, and it cannot be closely combined with the semiconductor device.
[0015] In order to make the glass powder of the present invention uniformly crystallized, the zinc oxide-containing crystalline powder also includes ZnO, 2ZnOSiO 2 、ZnOB 2 O 3 、3ZnOB 2 O 3 、4ZnO 3 B 2 O 3 At least one of .
[0016] After crystallization, the glass powder of the present invention has a thermal expansion coefficient of 2.5×10 -6 ~4.0×10 -6 / ℃, when covered on the silicon wafer of semiconductor element material, no warping and cracking will occur.
[0017] In addition, the present invention also provides a use of the lead-free powder glass in preparing a surface stabilizing material for a mesa-type semiconductor device.
[0018] In the past, many methods for applying glass powder to semiconductor devices have been studied and used. However, the knife scraping method, electrophoresis method and photolithography spin method are generally used now. The knife scraping method is the simplest and most convenient method, but because it is mixed with an organic solvent containing a small amount of resin, it is difficult to completely remove the resin. For example, in a mesa semiconductor, there is a problem that the glass powder at the edge of the mesa groove becomes thinner, resulting in poor forward and reverse withstand voltage. Although the photolithography spin method can form a thicker glass powder at the edge of the mesa groove, it contains a large amount of photoresist, which makes it difficult to remove the photoresist and has poor electrical properties. Therefore, the electrophoresis method is recommended when using the glass powder of the present invention for the following two reasons: First, the glass powder is selectively applied only to the mesa groove by the electrophoresis method, and the influence of the chemical treatment in the process of removing the glass attached to the outside of the mesa groove in the later process is less, and the final yield is improved. Second, the electrophoresis method does not contain any organic resin components, and by selecting a suitable electrolyte, a thick and firm glass powder film can be formed at the edge of the mesa, thereby making the forward and reverse withstand voltage higher.
[0019] Through the above technical solution, the present invention achieves the following beneficial effects: 1. The glass powder provided by the present invention is prepared by mixing ZnO, B 2 O 3 、SiO 2 SnO 2 、In 2 O 3 、ZrO 2 、TiO 2 、Bi 2 O 3 ,La 2 O 3 、Nd 2 O 3 The appropriate ratio of each component and the introduction of Y 2 O 3 ,GeO 2 To homogenize the glass, introduce Zn 4 B 6 O 13 、Zn 3 B 2 O 6 、Zn 3 (BO 3 ) 6 、Zn 4 O(BO 2 ) 6 , ZnB 4 O 7 、Zn(BO 2 ) 2Crystalline powders containing zinc oxide make the glass powder have a small crystal size and improve the electrical properties, so that the glass powder can be sintered and crystallized at a relatively low temperature of 700-750°C. After crystallization, the thermal expansion coefficient is close to that of the semiconductor material silicon wafer, which will not cause the silicon wafer to warp or crack, and the reverse withstand voltage is relatively high.
[0020] 2. The glass powder of the present invention does not contain environmentally harmful lead. In addition, although antimony has been used in zinc-based glass powder, the present invention does not contain antimony because of restrictions on harmful ingredients. Zinc-based glass powders have also contained aluminum oxide, but aluminum oxide increases the thermal expansion coefficient, so the present invention does not contain aluminum oxide. Of course, it does not contain alkaline impurities such as Na, K, and Li, and metal impurities such as Fe, Cr, and Cu that have adverse effects on semiconductor devices. DETAILED DESCRIPTION
[0021] The specific implementation of the present invention is described in detail below in conjunction with the examples. It should be understood that the specific implementation described herein is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0022] Table 1 and Table 2 are the ingredients and amounts of Examples and Comparative Examples, respectively.
[0023] Table 1 Ingredients and dosage of the examples (unit: g)
[0024] Table 2 Comparative Example Ingredients and Dosages (Unit: g)
[0025] The preparation method of glass powder is as follows: first, the base material powder is uniformly mixed, and then melted at 1200-1400°C for 1-2 hours to vitrify it. After the molten glass is rapidly cooled, it is put into a ball mill and crushed into powder, and then a crystal containing zinc oxide is added and uniformly mixed to obtain glass powder for semiconductor devices.
[0026] Performance Testing Thermal expansion coefficient: The average thermal expansion coefficient of the sintered product after sintering and crystallization at 700-750°C was measured by TMA at 30-300°C.
[0027] Warping of the chip when covering the semiconductor device: The glass powder is applied to the 4-inch table-type forward and reverse rectifier diodes with a withstand voltage of 1000V by electrophoresis, and the judgment is made after it is sintered and crystallized. The chip that is completely free of warping is indicated by ○, and the chip that is severely warped and cracked is indicated by ×.
[0028] Reverse withstand voltage: The electrical characteristics of the semiconductor element are evaluated by a curve plotter. The reverse withstand voltage of the rectifier diode when the current value is 10μA, and those that show 1000V or above are qualified.
[0029] The performance test results are shown in Table 3.
[0030] Table 3 Performance test results
[0031] From Table 3 we can see that: (1) The glass powder composition of the example meets all the requirements. The evaluation results of the 4-inch rectifier diode show that there is no chip warping in the semiconductor device, the electrical characteristics are also good, and the reverse withstand voltage reaches 1000V.
[0032] (2) Comparison of Example 10 and Comparative Example 1. SiO 2 When the content of ZnO increases, it is difficult to crystallize. The amount of ZnO added is also very small, 0.1%, so the thermal expansion coefficient becomes higher and the warpage becomes larger. At the same time, the electrical properties are not good.
[0033] (3) Comparison of Example 7, Comparative Example 2 and Comparative Example 3, SiO 2 The content of Y 2 O 3 , the crystals contain ZnO and Zn 4 B 6 O 13 Therefore, dense crystals are uniformly precipitated and the electrical properties are good; although Comparative Example 2 contains Y 2 O 3 , but the crystallized product is only ZnO. Although uniform crystals are precipitated, the particle size is large and not dense, so the electrical properties are poor; while Comparative Example 3 does not contain Y 2 O 3 , and the crystallized material is only ZnO, which cannot precipitate dense and uniform crystals, has a large thermal expansion coefficient, causes warping and has poor electrical properties.
[0034] (4) Compare Example 7 with Comparative Example 4. In Comparative Example 4, SiO 2 More than 20%, but not containing Y 2 O 3 or GeO 2 , so the glass is not uniform. The crystals contain Zn 3 B 2 O 6 However, it does not precipitate dense and uniform crystals, has a large thermal expansion coefficient, large warping, and poor electrical properties.
[0035] (5) Comparison of Example 10 and Comparative Example 5. The particle size distribution of Comparative Example 5 has a coarse particle size D50 of 15 μm, which makes it difficult to produce dense and uniform crystals, has a large thermal expansion coefficient, large warpage, and poor electrical properties.
[0036] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0037] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0038] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A lead-free powder glass for surface stabilization of a mesa-type semiconductor device, characterized in that: The invention comprises a base material powder and a zinc oxide crystalline powder. The base material powder comprises ZnO 50-70%, B2O 35-22%, SiO 15-25%, R x O y 0.01~5%, and Y2O3 and / or GeO20~15%, among which R x O y At least one of SnO2, In2O3, ZrO2, TiO2, Bi2O3, La2O3, Nd2O3; the zinc oxide crystalline powder is Zn4B6O 13 , at least one of Zn3B2O6, Zn3(BO3)6, Zn4O(BO2)6, ZnB4O7, and Zn(BO2)2, relative to 100g of substrate powder, the amount of the zinc oxide-containing crystalline powder is 0.01~5g, and the D50 particle size of the powder glass is 1~10μm.
2. The lead-free powdered glass according to claim 1, characterized in that: The zinc oxide-containing crystalline powder also includes at least one of ZnO, 2ZnOSiO2, ZnOB2O3, 3ZnOB2O3, and 4ZnO3B2O3.
3. The lead-free powdered glass according to claim 1, characterized in that: The content of ZnO in the base material powder is 55-70%.
4. The lead-free powdered glass according to claim 1, characterized in that: The base material powder has R x O y The content is 0.01~3%.
5. The lead-free powdered glass according to claim 1, characterized in that: In the base material powder, the content of SiO2 is 20-25%, and the content of Y2O3 and / or GeO2 is not zero.
6. The lead-free powdered glass according to claim 1, characterized in that: The content of the zinc oxide-containing crystalline powder is 0.01-3 g relative to 100 g of the base powder.
7. The lead-free powdered glass according to claim 1, characterized in that: After crystallization, the average thermal expansion coefficient of the powder glass in the temperature range of 30°C to 300°C is 2.5×10 -6 ~4.0×10 -6 / ℃.
8. Use of the lead-free powder glass according to any one of claims 1 to 7 in preparing a surface stabilizing material for mesa-type semiconductor devices.